INTERACTIVE POWTOON MEDIA BASED ON CONSERVATION OF THE INTEGRITY NKRI CONTENT TO IMPROVE LEARNING OUTCOMES FOR FIFTH-GRADESELEMENTARY SCHOOL - Artha, Alfian Nur; Setyasto, Novi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
Innovative and interactive learning media can optimize Civics learning. Based on pre-research data at First Bandungan Public Elementary School, various problems arise, one of which is the need for more utilization of learning media, which makes the learning environment less enthusiastic and affects the low learning outcomes of students. This study aimed to develop the feasibility and effectiveness of Conservation-based Interactive Powtoon animated video learning media on Civics subject matter on maintaining the integrity of the Republic of Indonesia in fifth-grade First Bandungan Public Elementary School. This type of research uses the type of Research and Development (R&D) with the development model, namely Borg and Gall 8 stages. Data collection techniques in the form of tests and non-tests. The results showed that the media developed was worthy, as evidenced by several experts. Proven by the presentation of the presentation by the media expert of 88%, the grammar by the linguist of 91%, and the content component by the content expert of 86%. Media that effectively increase student motivation and learning outcomes is shown by the t-test with a. sig (2-tailed) value of 0.000 <0.05, and the N-gain average increase test of 0.388 shows moderate criteria. Conservation-based interactive Powtoon animation video media can stimulate student learning to be more enthusiastic and motivated.